Some new contributions to neutrinoless double-β decay in an SU(2)×U(1) model - Escobar, C. O.; Pleitez, V. (American Physical Society (APS), 1983)
We consider an SU(2)×U(1) model having both Dirac and Majorana mass terms for the neutrinos, with an extended Higgs sector without natural flavor conservation. Under these conditions, we show that for a certain range of the mass parameters of the model, some new contributions become important for neutrinoless double- decay [()0]. © 1983 The American Physical Society.